2021
DOI: 10.1016/j.resuscitation.2021.05.006
|View full text |Cite
|
Sign up to set email alerts
|

Coronary angiography findings in patients with shock-resistant ventricular fibrillation cardiac arrest

Abstract: Introduction: Shock-resistant ventricular fibrillation (VF) poses a therapeutic challenge during out-of-hospital cardiac arrest (OHCA). For these patients, new treatment strategies are under active investigation, yet underlying trigger(s) and substrate(s) have been poorly characterised, and evidence on coronary angiography (CAG) data is often limited to studies without a control group.Methods: In our OHCA-registry, we studied CAG-findings in OHCA-patients with VF who underwent CAG after hospital arrival. We co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

2
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 40 publications
2
8
0
Order By: Relevance
“…12,19 Notably, other studies with similar inclusion criteria have reported comparable rates of survival to discharge of ≈70% for all patients with OHCA and shockable rhythm, and 60% for those with refractory VF/pVT. 3,20…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations
“…12,19 Notably, other studies with similar inclusion criteria have reported comparable rates of survival to discharge of ≈70% for all patients with OHCA and shockable rhythm, and 60% for those with refractory VF/pVT. 3,20…”
Section: Discussionmentioning
confidence: 99%
“…3 Patients in this cohort have prolonged low-flow duration, may never attain return of spontaneous circulation (ROSC), and have a heightened risk of short-term mortality in excess of 80% with equally adverse neurological outcomes. 2–4…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Importantly, ACO constitutes a major cause of difficult-to-defibrillate VF. 23,24 Especially this group with a treatable underlying cause may constitute a target population for early hospital transportation in case of refractory VF, with support of a mechanical resuscitation devices or ECMO. In case of confirmative data, additional optimisation of the diagnostic algorithms is needed, which requires multiple datasets on larger populations.…”
Section: Discussionmentioning
confidence: 99%